Think outside: positive risk-taking with people living with dementia. Issue 3 (11th September 2017) - Mapes, Neil
Abstract : Purpose: The purpose of this paper is to share findings from the evaluation of dementia adventure (DA) holidays provided in 2016 and drawing on these data, to share reflections on positive risk-taking, which are inherent in outdoor activities, and consider the implications for research and practice with people with dementia. Design/methodology/approach: Data are drawn from the 2016 internal evaluation report, using mixed methods design, of DA holidays independently reviewed by Dr Ruth Bartlett at the University of Southampton. Findings: DA holidays are leading to a range of social, emotional and physical well-being outcomes, as well as wider benefits for the community of people with dementia, their family and carers. Practical implications: Drawing on what positive risk-taking means for individuals, families and organisations, top ten considerations for positive risk taking outdoor activities are presented. Originality/value: The number of organisations providing adventure experiences and holidays for people with dementia in the UK remains very low with just a handful of organisations. The impact and evaluation of these holidays is just emerging and whilst compelling needs replication, with larger sample sizes supported by clinical and scientific expertise to deepen our understanding of the impact of positive risk-taking outdoor activities. Additionally, there is a need for thinking and acting differently summarised by the phrase "THINK OUTSIDE" in developing a wide range of nature based positive risk-taking activities with people with dementia.